The Relationship Between Mothers' Knowledge and the Implementation of Endorphin Massage in Reducing Postpartum Pain at Alisah Clinic - Ermita Silvana Putri (International Journal of Public Health Excellence (IJPHE), 2025)
Health is a state of well-being of body, mind, and social life that enables every individual to live productively in social and economic terms. Childbirth is the series of events involving the delivery of a baby that has developed sufficiently in the mother's womb, followed by the expulsion of the placenta and fetal membranes from the mother's body. The main problem commonly reported by women in labor is pain. One non-pharmacological management method to reduce labor pain is endorphin massage. The purpose of this research is to determine the Relationship Between Mothers' Knowledge and the Implementation of Endorphin Massage in Reducing Postpartum Pain at Alisah Clinic in 2025. This research is an analytical survey with a cross-sectional approach. The population in this study consisted of 35 postpartum mothers. The sample in this study used total population sampling, where the entire population of 35 individuals was taken as the sample. The results show that the majority of mothers had a low level of knowledge, totaling 21 individuals (60%), while the minority had a good level of knowledge, totaling 2 individuals (5.7%). The majority of mothers did not implement endorphin massage to reduce postpartum pain, totaling 31 individuals (88.6%), while the minority did implement it, totaling 4 individuals (11.4%). There is a Relationship Between Mothers' Knowledge Level About Postnatal Massage and the Benefits of Postnatal Massage During the Postpartum Period at AR Razi Clinic in 2025, as indicated by a Sig. value of 0.000 < α value of 0.05. The conclusion of this research is that there is a Relationship Between Mothers' Knowledge and the Implementation of Endorphin Massage in Reducing Postpartum Pain at Alisah Clinic in 2025. It is recommended that mothers increase their knowledge, specifically regarding endorphin massage, to reduce postpartum pain